A novel pH–precursor–glucose synergic control strategy for dinactin biosynthesis by an arctic actinomycete Streptomyces sp. Issue 12 (December 2016) - He, Hao; Xue, Ying; Xu, Ning; Yin, Ying; Lu, Jian; Cai, Menghao; Zhang, Yuanxing
Graphical abstract: Highlights: pH greatly affected dinactin biosynthesis in bioreactor. A pH precursor-combined strategy highly improved dinactin biosynthesis. A synergic pH–precursor–glucose regulation strategy further improved dinactin biosynthesis. Overexpression of nons gene improved dinactin biosynthesis based on the synergic strategy. Abstract: Dinactin, a macrotetrolide antibiotic produced by Streptomyces sp. R-527F, has attracted much attention in the ongoing pharmaceutical research because of its potential immunosuppressive properties. The aim of this study was to develop a robust fermentation platform for dinactin production. In the first step, we found that dinactin biosynthesis was significantly affected by pH that could be optimally controlled at 5.2–5.5. In this pH-regulated condition, dinactin production reached 124 mg/L, which was 1.8-fold of the control. Subsequently, we developed a feeding strategy based on the precursor sodium succinate in combination with pH control and obtained dinactin production of 291 mg/L, which was 4.22-fold of the original control. Furthermore, glucose-feeding strategies were designed based on the pH precursor regulation results, allowing dinactin production of 343 mg/L, which was 4.97-fold compared to the original conditions. Finally, the establishment of an engineered strain overexpressing the nonS gene encoding for the closure of the tetrahydrofuran ring in dinactin biosynthesis and its cultivation on the pH–precursor–glucose regulation platform yielded 382 mg/L dinactin, which further increased the yield by 11% as compared to the wild type under the same conditions. The designed bioprocess strategy holds the potential for large-scale production of dinactin.